Burned - Dixon, Franklin W. (New York : Aladdin Paperbacks, 2005)
Frank and Joe try to stop the illegal international CD- burning operation that employs teenagers.
8-12.
Keywords: Hardy Boys (Fictitious characters) -- Juvenile fiction; Detective and mystery stories